Diagnostic accuracy of preoperative computed tomography used alone to detect lymph-node involvement at radical nephrectomy. (April 2014) - Connolly, Stephen S.; Raja, Aditya; Stunell, Helen; Parashar, Deepak; Upponi, Sara; Warren, Anne Y.; Gnanapragasam, Vincent J.; Eisen, Tim
Abstract: Objective. The aim of this study was to compare preoperative computed tomography (CT) with pathological findings in patients undergoing lymphadenectomy at the time of nephrectomy for renal cancer-associated lymphadenopathy. Materials and methods. Data from 515 consecutive nephrectomy surgeries (2004–2012) in a single university-affiliated centre were analysed to identify patients who had undergone lymph-node dissection concomitant with nephrectomy. Preoperative CT imaging was subjected to multiple repeated independent blinded reviews (two radiologists and one surgeon, each individually and on two separate occasions). Retroperitoneal lymph-node status was subjectively categorized (in a manner not based purely on size criteria) at each review as: 1 = unequivocally positive, 2 = equivocally positive, 3 = equivocally negative, or 4 = unequivocally negative. These findings were compared with pathological analysis, and interobserver and intraobserver agreement was assessed using non-weighted kappa () statistics. Results. In total, 71 patients were stratified as category 1 ( n = 18), 2 ( n = 14), 3 ( n = 31) and 4 ( n = 8); pathological lymph-node metastasis was present in 14 (78%), four (28%), four (13%) and zero patients, respectively. Sensitivity, specificity, positive and negative predictive values for preoperative CT were 82%, 71%, 56% and 90%, respectively. Intraobserver agreement was greater for the radiologists (values 0.490, 0.540) than for the surgeon (value 0.393). Interobserver agreement was strongest for radiological category 1 (unequivocally positive; value 0.75). Receiver operating characteristics curves did not reveal significant differences in any observer accuracy. Conclusion. Contrary to concerns about a high false-positive rate, metastasis within regional lymph nodes can be predicted with reasonable accuracy by preoperative CT imaging alone.